Pengaruh Profitabilitas, Ukuran Perusahaan, dan Rotasi Audit terhadap Earning Manipulation (Studi Empiris pada Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia) - Syauqy, Muhammad Fadlan (Jurnal KIAFE, 2025)
This study aims to examine the effect of profitability, company size, and audit rotation on earning manipulation in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This study employs an associative quantitative approach using panel data regression analysis. The population consists of 37 transportation and logistics companies, with 28 companies selected as the final sample using purposive sampling, resulting in 84 firm-year observations. Data analysis was conducted using EViews version 12. Earning manipulation was measured using the Beneish M-Score model, while profitability, company size, and audit rotation were used as independent variables. The results indicate that profitability has a positive and significant effect on earning manipulation. Meanwhile, company size and audit rotation do not have a significant effect on earning manipulation. Simultaneously, profitability, company size, and audit rotation have a significant effect on earning manipulation. These findings suggest that profitability pressure may become an important factor associated with earning manipulation practices, while company size and audit rotation alone are insufficient indicators to explain such practices in transportation and logistics companies in Indonesia.